Religion and development: African traditional religion's perspective - Awuah-Nyamekye, Samuel (Religious Studies and Theology, 2012)
Unlike several decades after the World War II, there is now a growing recognition of the importance of religion for designing development programmes and projects. However, the involvement of religions of the indigenous peoples is not given the desired attention. This article, therefore, aims at presenting African traditional religion’s voice in this important discourse by using the traditional Akan people of Ghana as a case study. Despite its suffering from stereotyping, African traditional religion continues to play a critical role in the life of the traditional African. The term “Development” is not easy to define, the divergent theories on it point to this fact. The traditional Akan people’s understanding of development, however, is derived from their religious worldview. The institution of chieftaincy, gerontocracy, institution of taboos, kinship ties and their attitude towards nature are the main development mechanisms among the Akan. Despite the threats these mechanisms are undergoing today, the potential of these indigenous mechanisms for development is not in doubt, hence the need for further research.
free
Keywords: Akan (African people); Chiefdoms; Economic development – Religious aspects; Economic development – Social aspects; Human beings – Relation to nature; Indigenous peoples – Africa; Leadership; Religious – African religions; Nature – Religious aspects – African religion